2018
DOI: 10.3892/ijo.2018.4425
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MAGEA4 in primary lung cancer depends on subcellular localization and p53 status

Abstract: Melanoma antigen family A4 (MAGEA4), a cancer/testis antigen, is overexpressed and is thus an immunotherapy target in various malignant tumors, including non-small cell lung cancer. However, whether MAGEA4 induces or inhibits the apoptosis of lung cancer cells remains controversial, as is its prognostic significance, particularly since there is no reliable method with which to detect MAGEA4 specifically. In this study, we optimized assay conditions to detect MAGEA4 based on cells transiently transfected with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Growing evidence supports MAGEA protein involvement in the regulation of the processes that underlie cancer cell survival, tumor formation, and metastasis [37,38]. For instance, MAGEA4 inhibits the apoptosis of cancer cells by suppressing endogenousp53, or by enhancing malignant progression via p53-independent pathways [39]. Simultaneously, the overexpression of TWIST1, a bHLH transcription factor, may transcriptionally up-regulate the expression of MAGEA4 to activate cancer cell migration-invasion program [40].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports MAGEA protein involvement in the regulation of the processes that underlie cancer cell survival, tumor formation, and metastasis [37,38]. For instance, MAGEA4 inhibits the apoptosis of cancer cells by suppressing endogenousp53, or by enhancing malignant progression via p53-independent pathways [39]. Simultaneously, the overexpression of TWIST1, a bHLH transcription factor, may transcriptionally up-regulate the expression of MAGEA4 to activate cancer cell migration-invasion program [40].…”
Section: Discussionmentioning
confidence: 99%
“…MAGEA4 also seems to inhibit TP53‐dependent apoptosis. Furthermore, it has been demonstrated that nuclear MAGEA4 expression in the absence of nuclear TP53 expression results in poorer survival of NSCLC patients compared with cytoplasmic MAGEA4 [45]. As we did not analyze the subcellular localization of the CTAs in tumor samples, this could be one factor in why we failed to observe any difference in survival between patients with high or low CTA expression.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, MAGEA 4 is a cancer/testis antigen that is overexpressed in various types of malignant tumors and is an immunotherapy target. 20 Highly expressed MAGEA 4 is associated with a poor prognosis with a lower than five-year survival rate for osteosarcoma. 21 ID3 and ID1 are the other two genes that were upregulated in NHEM-c cells driven by melanoma A375exo.…”
Section: Discussionmentioning
confidence: 99%